Formulasi Blush on Stick Ekstrak Daun Karamunting (Rhodomyrtus tomentosa) Dengan Variasi Konsentrasi Biji Kesumba Keling (Bixa orellana L.) dan Carnauba Wax - M. Andi Chandra; Nur Rahmiati; Fairuz Yaumil Afra; Dyera Forestryana; Alya Raihanatha (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the physical characteristics, stability, and level of liking of blush stick preparations based on karamunting leaf extract with variations of kesumba keling seeds with a concentration of 0.5-2.5% and variations of carnauba wax with a concentration of 10-18%. This research is experimental with five different formulas. Evaluation was done through organoleptic test, homogeneity, pH, polishability, spreadability, cracking and hedonic test. Physical stability was tested using the cycling test method. Based on the results of the organoleptic characteristics test, the preparation has a stick shape, color from bright yellow to reddish orange, soft to moderately firm texture, and a distinctive aroma. The preparation is homogeneous, has a pH of 6.64-6.89, good polishability, spreadability of 3-3.5 cm, and does not crack. Based on the hedonic test, formula V was the most preferred in terms of color, aroma and texture. In the pre-cycling test and post-cycling test, there was no significant difference. The conclusion of this study, all blush on stick formulas were stable during 12 days of storage and formula V was chosen as the most optimal formula.